2008
DOI: 10.1007/s10038-008-0341-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between polymorphisms in SLC30A8, HHEX, CDKN2A/B, IGF2BP2, FTO, WFS1, CDKAL1, KCNQ1 and type 2 diabetes in the Korean population

Abstract: According to recent genome-wide association studies, a number of single nucleotide polymorphisms (SNPs) are reported to be associated with type 2 diabetes mellitus (T2DM). The aim of the present study was to investigate the association among the polymorphisms of SLC30A8, HHEX, CDKN2A/B, IGF2BP2, FTO, WFS1, CDKAL1 and KCNQ1 and the risk of T2DM in the Korean population. This study was based on a multicenter casecontrol study, including 908 patients with T2DM and 502 non-diabetic controls. We genotyped rs1326663… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
86
3
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 142 publications
(103 citation statements)
references
References 36 publications
12
86
3
2
Order By: Relevance
“…Especially, they were all located within CDKAL1 gene except for an intergenic variant of rs5015480 near HHEX gene. The association of the CDKAL1 gene concurred with the results from previous studies with American, 1 British, 5 French, 3 Danish, 4 Finnish, 2 Swedish, 1 Icelandic, 4 Korean, 9 Japanese, 10 and Chinese [11][12][13] populations. The significantly associated variants of the gene in the current study were specifically corresponding to those found in previous studies of Horikawa et al 14 and Wu et al 11 for rs7756992 and Zeggini et al 5 and Wu et al 11 for rs9465871 and rs10946398, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Especially, they were all located within CDKAL1 gene except for an intergenic variant of rs5015480 near HHEX gene. The association of the CDKAL1 gene concurred with the results from previous studies with American, 1 British, 5 French, 3 Danish, 4 Finnish, 2 Swedish, 1 Icelandic, 4 Korean, 9 Japanese, 10 and Chinese [11][12][13] populations. The significantly associated variants of the gene in the current study were specifically corresponding to those found in previous studies of Horikawa et al 14 and Wu et al 11 for rs7756992 and Zeggini et al 5 and Wu et al 11 for rs9465871 and rs10946398, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…4,7,[9][10][11] In particular, we selected six genes that showed reproducible associations with T2DM in cross-sectional studies in Korea. [19][20][21][22] The selected genes were as follows: KCNQ1 rs2237892, CDKAL1 rs7554840, CDKN2A/B rs1081161, SCL30A8 rs13266634, TCF7L2 rs7903146 and PPARG rs1801282.…”
Section: Gene and Snp Selectionmentioning
confidence: 99%
“…The estimated powers of our study were 97%, 72%, 98% and 39% for rs2237892 (KCNQ1), rs7754840 (CDKAL1), rs10811661 (CDKN2A/B) and rs13266634 (SLC30A8), respectively, in the recessive genetic model and 92%, 84%, 85%, 61%, 85% and 41% for rs2237892 (KCNQ1), rs7754840 (CDKAL1), rs10811661 (CDKN2A/B), rs13266634 (SLC30A8), rs7903146 (TCF7L2) and rs1801282 (PPARG), respectively, in the dominant genetic model, based on the reference odds ratios and allele frequencies from previous studies. 15,21,23 Po0.05 was considered statistically significant.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…본 저자의 연구결과 대부 분의 제2형 당뇨병 관련 유전자 즉 TCF7L2, SLC30A8, HHEX, CDKAL1, CDKN2A/B, KCNQ1 유전자 변이가 이식 후 당뇨병 발생에서도 유의한 연관관계를 보였다 [14]. TCF7L2 rs7903146 [14,15], SLC30A8 rs13266634 [14,16], HHEX rs1111875, HHEX rs7923837, HHEX rs5015480, CDKAL1 rs10946398, CDKN2A/B rs10811661 [14,17] [10,13,30]. Calcineurin억제제는 인슐린 저항성을 증가시 키는 부분도 있지만 췌장의 베타세포에 독성을 나타내어 인슐린 분비능을 저하시킴으로써 혈당을 상승시키는 부분 이 더 중요할 수 있다 [31].…”
Section: 유전자unclassified